Extraction of petrol products from water by magnetite-based sorbents - Радовенчик, Вячеслав Михайлович; Романенко, Марина Іванівна; Гринчук, Софія Василівна; Глущенко, Анастасія Станіславівна (Eastern-European Journal of Enterprise Technologies, 2015)
The results of studying the effectiveness of petroleum extraction from water by their sorption on magnetite particles are given. It was found that magnetite particles, obtained by chemical condensation have the high dispersion ability, which prevents their practical use in industrial processes. It is possible to significantly change the particle size distribution of the magnetite mixture by treating them with petroleum products followed by ignition at high temperatures. The main factors, affecting particle size distribution of the mixture after such treatment is dose of petroleum products, the temperature and duration of mixture ignition. It was determined that the optimum ignition temperature is 300°С, at which the largest number of aggregates with sizes of 30 - 40 microns is produced. Particle size distribution is significantly affected by the ignition duration that we associate with the residual content of petroleum products that do not manage to decompose under short ignition duration and act as a binder for magnetite particles. At low doses (ratio of petroleum products: magnetite within 0.083 - 0.025), there was no significant effect on the particle size distribution of the treated mixture. In certain circumstances, the number of sorption: ignition cycles does not affect the particle size distribution of the mixture, allowing to form filtering media with stable hydraulic and sorption properties.